Human Rights Protection in the Context of Religious Diversity in Indonesia - Mixra Kristiani Gulo; Versi Eleven Waruwu; Ita Febrin Nasrani Zalukhu; Besti Zebua; Fiktor Daeli; Iman setiaman Zai; Zoni Zai; Hedrikus Otniel Nasozaro Harefa (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Indonesia, as a country with a high level of religious diversity, faces complex dynamics in ensuring the protection of Human Rights, particularly freedom of religion and belief. Religious diversity, which includes Islam, Protestantism, Catholicism, Hinduism, Buddhism, and Confucianism, constitutes a social asset that has the potential to strengthen national unity; however, it also gives rise to various challenges such as intolerance, discrimination, and religion-based violence. This article aims to examine the relationship between human rights principles and religious diversity in Indonesia, identify obstacles to the implementation of freedom of religion, and analyze the roles of the government and society in fostering a tolerant and inclusive social life. The findings indicate that strengthening human rights protection within the context of religious diversity requires fair and inclusive regulations, continuous multicultural education, and the development of interfaith dialogue as a means of building mutual understanding and respect for differences.